Influence of Pb2+ doping in the optical and electro-optical properties of SnO2 thin films - dos Santos, Stevan B.O. [UNESP]; Boratto, Miguel H. [UNESP]; Ramos, Roberto A. [UNESP]; Scalvi, Luis V.A. [UNESP] (Elsevier, 2022)
Different types of doping incorporated to tin dioxide (SnO2) have been reported in order to control its bandgap aiming optoelectronic applications, such as transparent electrodes, solar cells and displays. In this work, the doping of SnO2 with lead in the oxidation state 2+ (Pb2 +) is investigated, in conjunction with the influence on the optical and electro-optical properties of thin films, deposited by sol-gel-dip-coating. It was observed that for an insertion up to 25 at% of lead, there is no formation of a secondary crystalline phase beyond the rutile phase of SnO2. Optical characterization data indicate two behavior tendencies: for doping level up to 1 at%, Pb2+ enters preferentially as interstitial impurity, whereas for higher doping it enters substitutional to Sn4+. For doping up to 1 at% the bandgap increases due to the Burnstein-Moss effect, in addition to a decrease in the capture energy for metastably photoexcited electrons. On the other hand, for doping above 1 at%, there is an increase in the Urbach energy, shifting the energy level of the valence band, leading to a decrease in the bandgap from 3.45 to 2.89 eV, which shows potential applicability in bandgap engineering. The higher doping level also increases the capture energy for photoexcited electrons and gives rise to the persistent photoconductivity effect at low temperatures, related to a large lattice relaxation around the dominant photoexcited defect.
Keywords: Bandgap engineering; Capture energy; Pb2+ doped SnO2; Persistent photoconductivity; Urbach energy